2019
DOI: 10.1016/j.dib.2019.104125
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput mass spectrometry and bioinformatics analysis of breast cancer proteomic data

Abstract: Data present here describe a comparative proteomic analysis among the malignant [primary breast tumor (PT) and axillary metastatic lymph nodes (LN)], and the non-tumor [contralateral (NCT) and adjacent (ANT)] breast tissues. Protein identification and quantification were performed through label-free mass spectrometry using a nano-liquid chromatography coupled to an electrospray ionization–mass spectrometry (nLC-ESI-MS/MS). The mass spectrometry proteomic data have been deposited to the ProteomeXchange Consorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Moreover, cytofluorometric analyses suggested that breast cancer cells were driven toward late apoptosis and necrosis in a dose-and time-dependent manner. The involvement of the apoptotic pathway was further verified by IPA software [35], which showed that the most affected canonical biological pathway was apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cytofluorometric analyses suggested that breast cancer cells were driven toward late apoptosis and necrosis in a dose-and time-dependent manner. The involvement of the apoptotic pathway was further verified by IPA software [35], which showed that the most affected canonical biological pathway was apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Tang et al studied 65 breast tumors and 53 adjacent noncancerous tissues with extensive fractionation, leading to 118 RAW files [20]. Gomig et al studied primary breast tumors, axillary metastatic lymph nodes and contralateral and adjacent breast tissues from seven patients, leading to 69 RAW files [21]. Lawrence et al studied 20 breast cancer cell lines and four primary breast tumors, leading to 450 RAW files [22].…”
Section: Evaluation Of the Protein Sequencing Depthmentioning
confidence: 99%
“…The number of proteins enriched by each pathway by the DIA method was much greater than those enriched by the DDA method (Figure 4D). Furthermore, to investigate the association between the significantly changed proteins and lung cancer disease, we used IPA software (IPA, QIAGEN, Redwood City, CA) to analyze the differential proteins from the DDA and DIA strategies, respectively [15]. Sixty-eight differ-ential proteins in lung cancer were identified using both methods.…”
Section: Summary Of Differential Proteins In Lung Cancer Clinical Tis...mentioning
confidence: 99%